(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article is devoted to the study of the possibility of using a combined method of tuning typical regulators to control multivariate multilink dynamic objects with several controlled and controlling parameters. The designed combined regulator, built on the basis of the joint use of two methods of setting the parameters of the regulator, based on ensuring the autonomy of control channels, and taking into account the effects of cross channels in static, has the properties of structural stability and rudeness to errors of the model of the control object. Invention proposes automated method of finding optimal parameters of regulators for multivariate multilink objects with lag property and high inertia. The disclosed method enables real-time operational control of multidimensional dynamic objects. The developed combined method of tuning multidimensional standard regulators makes it possible to calculate the parameters of regulators, taking into account the limitations of control influences and a number of engineering requirements for transients.